Disentangling the influence of the economic development discourse on the management of national parks through systems thinking: Case studies from the Philippines and Mozambique. (February 2023) - Horigue, Vera; Richards, Russell; Taju, Alima; Maina, Joseph
Abstract: Globally, management of national parks has evolved to become more inclusive of stakeholders by incorporating socio-economic development objectives and shifting from strict protection to resource management. These strategies have worked in some contexts, but have also caused adverse unintended consequences such as ecosystem degradation and overexploitation inside many national parks in developing countries. The causes of these unintended consequences are usually overlooked by management effectiveness tools that fail to consider the governance context that underpins park management. We show that a better approach is to apply systems thinking when evaluating park management. Using systems thinking and the human ecology systems framework, we evaluated governance of two national parks in the Philippines and Mozambique to better understand the contextual factors and dominant discourses that underpin park management in developing countries. We found that our case studies were experiencing rapid environmental decline that was driven by the expansion of tourism, agriculture, and mining. We show that the economic development discourse, and delays in decision-making and responses have allowed these activities to rapidly increase inside and along the borders of both national parks. Furthermore, we show that the system structure is facilitating this pattern of behaviour, undermining management interventions aimed at protecting the environment. This study highlights the multi-dimensional tensions in park management that is applicable to all national parks. Specifically, it highlights the role of economic development policies of governments on national parks, and the importance of regulating human activities in and around national parks to minimise ecosystem degradation. Highlights: Systems thinking provides an effective framework for conservation evaluation. Systems diagrams summarises the key attributes influencing development in parks. Aspirations for economic growth undermine conservation objectives of parks. Reforms are needed to set limits inside parks and address unresponsive management.